Multivariate decomposition of trends, inequalities and predictors of skilled birth attendants’ utilisation in Nigeria (1990–2018): a cross-sectional analysis of change drivers (2022)
Objectives Literature has assessed skilled birth attendants (SBAs) utilisation, but little is known about what contributes to the changes in SBA use. Multivariate decomposition analysis was thus applied in this study to examine; levels, trends, inequalities and drivers of changes in SBA utilisation. Design and setting A cross-sectional analysis of five waves of NDHS-data (1990, 2003, 2008, 2013, and 2018), collected through similar multistage sampling across the 36 states and the federal-capital-territory of Nigeria. Participants Women of reproductive age (15–49 years), and with at least one birth in the last 5 years preceding each of the surveys .Main outcome measure SBA use is the response variable while explanatory variables were classified into; Demographics, Health, Economic and Corporal factors. Methods Chi-square test for trends of proportions across the ordered survey years assessed trends in SBA use. MDA that quantifies and partition predictors effect into endowment and coefficient components evaluated contributors to changes in SBA use. Statistical analysis was carried out at a 95% confidence interval in Stata 16. Results SBA use increased with significant (p<0.05) linear trends by 12% between 2003 and 2018. The decomposition analysis showed that differences in characteristics (endowment) accounted for 11.5% of the changes while the remaining 88.5% were due to differences in effects (coefficient). SBA utilisation rises by 61% when respondents decided on her health compared to when such decisions were made by the spouse. Utilisation of SBA, however, fell by 88% among women who reside in the states with high rural populations percentage. Conclusions SBA use remained low in Nigeria, and slowly increase at the rate of <1% yearly. Women health decision-making power contributed most to positive changes. Residing in states with high rural populations has a negative impact on SBA use. Maternal health programmes that strengthen women’s health autonomy and capacity building in rural communities should be encouraged.